حماية المقاتلين وغير المقاتلين في الشريعة الإسلامية دراسة في القانون الدولي الإنساني من المنظور الإسلامي مدعمة بالاتفاقيات الدولية - حوبه, عبد القادر (University of Eloued جامعة الوادي, 2015)
تتناول هذه الدراسة جانبا مهما في مجال القانون الدولي الإنساني من المنظور الإسلامي، فإذا كانت اتفاقيات القانون الدولي الإنساني قد بينت أصناف المقاتلين ووفرت لهم الحماية، كما وفرت الحماية إلى فئات ضحايا النزاعات المسلحة، فإن الشريعة الإسلامية قد تضمنت هذه القواعد، وكانت سباقة في إقرار هذه الحماية. This study deals with an important aspect in the field of international humanitarian law from the Islamic perspective. If the international humanitarian law conventions have shown varieties combatants and provided them with protection, as well as providing protection to victims of armed conflict categories, the Islamic law has included these rules, and has been a pioneer in the adoption of this protection
The protection of combatants and non-combatants in Islamic law Study of international humanitarian law from the Islamic perspective Supported by international conventions
مجلة البحوث والدراسات المجلد 12 العدد 01 جامعة الوادي
Keywords: الحماية، القتال، النزاع المسلح، الجهاد، الحقوق، العهود والمواثيق، الإنسانية، الرحمة; protection, fighting, armed conflict, Jihad, the rights, covenants and conventions, humanity, mercy